A la recherche d’espaces invisibles de la mobilité - Sandrine Depeau; Erwan Quesseveur (Netcom)
Resorting to GPS technics for collecting daily travel behaviors is knowing an important development. Indeed, those techniques allow to increase the space and time quality of data. However, their implementation in terms of collection and analysis still requires experimentation phases to permit data generalization. This article reports different phases of an experiment research resorting to GPS tracking of children’s daily travels in urban context. The survey carried out with children aimed on the one hand at testing "children’s acceptability" of traveling with a GPS. On the other hand, it was about going over the origin-destination approach by testing analyses concerning the daily travel space, which was estimated with three indicators: green impregnation, potential social attractiveness, road-split (road crossings).